Patient safety education in pre‐registration nursing programmes in South Korea. (2nd October 2020) - Lee, S. E.; Dathinten, V. Susan; Do, H.
Abstract : Aims: This study investigated how patient safety is currently taught in pre‐registration nursing programmes across South Korea and explored nurse educators' perspectives on curriculum change. Background: Pre‐graduate education plays a critical role in preparing nurses with the requisite patient safety competencies. However, little is known about how patient safety education is addressed in South Korean nursing schools or the perspectives of nurse educators regarding patient safety education and a need for change. Methods: This descriptive study used data collected during a 2019 accreditation workshop provided by the Korean Accreditation Board of Nursing Education. A paper‐and‐pencil survey was completed by 80 nurse educators working in 16 regions throughout Korea. Results: A little consistency was found in approaches to teaching patient safety. Patient safety topics are addressed throughout various nursing courses, and patient safety education is limited in hours of instruction and breadth of content. A majority of respondents indicated that additional supports are needed, including a national standardized curriculum for patient safety education. Conclusion: A new approach to teaching patient safety is needed in Korean pre‐registration nursing education. Overall, patient safety education is limited and provided through a fragmented approach with little attention to systems, workplace design or human issues that are necessary for developing the critical reasoning and skills to support patient safety. Implications for nursing policy: The accrediting and regulatory bodies in South Korea should work together to develop and implement explicit standards of patient safety education and patient safety competencies for nursing students. Development of a standardized national curriculum is essential for providing a consistent, systematic and comprehensive approach to patient safety education in nursing programmes.